Tutela del patrimonio culturale e monitoraggio dei vulcani in Italia : Le attività di NHAZCA nell’ambito del programma spaziale europeo IRIDE - Valerio, Emanuela; Pantozzi, Gianmarco; Scancella, Stefano; Chessa, Andrea; Ciracì, Enrico (GEOmedia, 2024)
IRIDE represents one of the most relevant European space programs in the field of Earth observation. Its implementation will take place in Italy on the initiative of the Government, thanks to the resources of the National Recovery and Resilience Plan (PNRR) integrated by the funds of the National Complementary Plan (PNC). In this context, the commitment of NHAZCA S.r.l. is focused on the protection of the national cultural heritage and on the monitoring of Italian volcanoes. To this purpose, the service aims to improve the understanding of the ground displacement processes that affect volcanic areas and which can have direct effects on our cultural heritage, using high resolution SAR (Synthetic Aperture Radar) data, acquired from the constellations Sentinel-1 (ESA), COSMO-SkyMed (ASI) and SAOCOM (CONAE - Comisión Nacional de Actividades Espaciales), and applying to them an Advanced SAR Differential Interferometry (A-DInSAR) technique. Therefore, starting from the deformation maps and time series obtained, the next step involves providing some tools that help the End-User in understanding and interpreting the data; these will involve the generation of specific geospatial products, which will consist of spatiotemporal anomaly maps, differential deformation maps and other useful statistical information.